GENE EXPRESSION SILENCING METHODS IN IN VITRO MODELS - Dorota, Michał; Dorota, Alicja; Żywiec, Wojciech; Karaban, Kacper; Maryniak, Nicole; Rzeszutek, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Gene expression silencing is one of the key tools in molecular biology and is widely applied in in vitro studies to investigate gene function and the mechanisms regulating cellular processes. The dynamic development of molecular techniques has resulted in the availability of numerous strategies that enable either transient or permanent reduction of gene activity at different stages of gene expression. The aim of this work is to review and compare gene expression silencing methods used in in vitro models, with particular emphasis on their mechanisms of action, efficiency, durability of the effect, and experimental limitations. The article discusses classical approaches based on RNA interference, including the use of siRNA, shRNA, and microRNA modulation, as well as strategies employing antisense oligonucleotides. Special attention is given to technologies based on the CRISPR system, including CRISPRi as a tool for reversible transcriptional repression and CRISPR–Cas9, which enables permanent disruption of gene function. Issues related to the delivery of molecular tools into cells, validation of silencing efficiency, and the importance of appropriate experimental controls are also addressed. Analysis of the literature indicates that the choice of an appropriate method should be tailored to the research objective, the characteristics of the gene under investigation, and the planned duration of the experiment. Increasingly, a complementary approach—combining different gene silencing strategies is recommended, as it enhances the reliability of results obtained in in vitro studies.